PENGEMBANGAN BAHAN AJAR E-LKPD BERBASIS PENGERINGAN IKAN ASIN PADA MATERI SUHU DAN KALOR FISIKA SMA - Kiki Dwi Trisnani; Subiki Subiki; Sri Astutik (JURNAL PEMBELAJARAN FISIKA, 2021)
The research carried out aims to develop teaching materials that are sontextual local wisdom in order to attract student in learning. The teaching materials that will be developed in this research are e-LKPD based on drying salted fish on temperatured and heat materials. The research method used in this research in the ADDIE development model. The ADDIE development model has five stages, namely Analysis, Design, Development, Implementation and evaluation. The research steps are carried out in accordanse with the ADDIE satges. The results of the research conducted, namely at the analysis stage, it was found that the lack of use of alternative teaching materials such as e-LKPD made student less interested during the learning process. Teaching materials that contain observation activities are meeded to improve psychomotor skills in students so that in this study the e-LKPD was developed by containing a simple experiment on drying salted fish. Preparation or writing of e-LKPD materials using the 3d pageflip application. This applicatin has the adavantage of complete features that make the 3d effect look real. This 3d pageflip appication requires a number of computer devices to use and the installation process is quite long. The constraints of this research are that the computer equipment owned by the researcher does not support the isntallation of the 3d pagefip application, the limited time of the study, and the limitation of the researcher in usng the 3d pageflip applicatin so that the research is only carried out until the sdesign stage.